The Effect of Increasing pH on Heavy Metal Content of Cu and Cd and Structure of the Gills and Coats of Anadara granosa with Scanning Electron Microscopy (SEM) Study - Isa Anzori; Delianis Pringgenies; Sri Redjeki (Jurnal Moluska Indonesia, 2019)
Significant changes in pH, both acidic and alkaline, can disrupt water quality. Furthermore, it will affect the life of aquatic biota. The purpose of this study was to determine the effect of increasing pH on heavy metal concentrations of Cu and Cd (quantitative) in shellfish bodies and on the level of damage to the gills and mantle shells (qualitative) by scanning electron microscopy. The research was conducted at the Integrated Marine Science Laboratory, UNDIP Semarang. Heavy metal analysis was carried out at Wahana Laboratorium Semarang. The scanning electron microscopy process was carried out at the Electron Microscopy Unit, Faculty of Medicine, UNAIR Surabaya. The results of the heavy metal analysis both Cu and Cd showed that pH 9 had the highest heavy metal content, namely Cu = 0.33 mg / kg while Cd = 0.57 mg / kg. Whereas for pH 7, the lowest heavy metal concentration was obtained for Cd = 0.35 mg / kg, but for the lowest Cu was found at pH 8 of 0.21 mg / kg. The differences were seen in the SEM results of gills and mantle ph 7 and 9. Observations on mantle epithelial cells and gill filaments with a magnification of 75 and 1000X showed that at pH 7 the epithelial cells had regular folds, the distance between the barriers was clear and the size was normal. Whereas at pH 9 it has irregular folds, the distance between the bulkheads is hollow and perforated. The gill filaments of pH 7 have a smooth filament structure and clear between the filaments.